Análise metabolômica do processo de encistamento de Acanthamoeba castellanii - Cecilia Cirelli dos Santos Ferreira (2018)
The free-living amoebae of the genus Acanthamoeba are ubiquitous protozoa that can eventually act as parasites, causing serious infections such as granulomatous amoebic encephalitis and amoebic keratitis. A relevant aspect of the pathophysiology of acanthamoebiasis is the ability of the protozoa to encyst on infected tissues. Acanthamoeba cysts present resistant double walls, resulting in lower efficacy of drugs, delay in the treatment and therapeutic failure. The encystment process is not entirely understood and the omics sciences can contribute to evaluate the phenotype of organisms. Thus, the aim of this work was to determine the metabolic profile of Acanthamoeba castellanii during the process of cell differentiation of trophozoites into cysts, since the omics sciences can contribute to the evaluation of gene expression and phenotype of organisms. Encystment was induced in a strain of A. castellanii in axenic culture with Neff saline, establishing the kinetics of pre-cysts and cysts formation. Time zero (throphozoites only), twenty-four hours (transformation initiated) and seventy-two hours (cysts only) cultures were submitted to extraction of metabolites for evaluation by gas chromatography coupled to mass spectrometry (GC/MS). Eighteen metabolites with statistical significance were identified, including amino acids, lipids, carbohydrates, nitrogen compounds and polyamines. In general, there was a reduction of the concentration of metabolites with the advance of the encystment, with the exception of arbutine, cellobiose and lactose. The results indicated a decrease of Acanthamoeba metabolism during encystment, as well as an alteration of its energy and carbon source. The involvement of ABC transporters in encystment was also suggested. They could act as exporters of degradation products from organelles and macromolecules during the process.